A Case Control Study on Physical Activity and Body Mass Index Associated with Hemorrhoids - Jalina Karim; Alif Asyraf Arispa Abdullah; A'syaratun Kamilah Zolkifle; Nur Shafizah Roslan; Suganthi Kumar; Kelvin C Shiong (Universitas Airlangga, 2020)
Introduction: Body mass index (BMI) and physical activity are the controversial risk factors that cause hemorrhoids. This study was conducted to determine the association between body mass index and physical activity. Methods: This was a case-control study which involved two hundred and two patients using convenience sampling. They had to answer a questionnaire consisting of the International Physical Activity Questionnaire (IPAQ) which monitored their physical activity and their BMI was also measured. For the descriptive analysis, Chi square and an odd ratio were carried out. Results: There was a significant association between age and hemorrhoids (p=0.02), in which the patients who were younger than 50 years old were more likely to have hemorrhoids compared to those who were older than 50 years old (OR=2.268, 95%CI: 1.107-4.630). For the risk estimation calculation, the Chinese individuals were found to have a higher risk compared to non-Chinese individuals (OR=2.056, 95% CI: 1.174-3.601). BMI was proven to be significantly associated with hemorrhoids (p=0.043). Physical activities were found to not be statistically significant (p=0.209). Those with a low and moderate physical activity level were 1.24 times more likely to have hemorrhoids compared to those with a high level of physical activity (OR=1.243, 95%CI:   0.697-2.217). The confidence interval was between 0.697 and 2.217, therefore it was not statistically significant. Conclusion: Physical activity was not associated with the hemorrhoids. However, it was shown that good physical activity could help to regulate bowel function and therefore, the occurrence of hemorrhoids would be less likely. BMI was significantly associated with hemorrhoids.